4CPS-111 Efectiveness and cost of abiraterone and enzalutamide in prostate cancer - Selvi, P (Eur J Hosp Pharm, 2018)
BACKGROUND: Abiraterone and enzalutamide are expensive drugs used in hospitals for metastatic prostate cancer and it is necessary to evaluate health outcomes from its use to establish whether it is cost effective PURPOSE: To analyse the effectiveness and cost of abitarerone and enzalutamide in asymptomatic or mildly symptomatic metastatic castration-resistant prostate cancer patients (mCRPC) to whom chemotherapy is not clinically indicated and in those whose disease has progressed after docetaxel chemotherapy regimen-based. MATERIAL AND METHODS: A retrospective descriptive study covering the period from January 2013 to June 2017 of mCRPC patients starting treatment with abiraterone or enzalutamide between January 2013 and June 2016 was performed. Parameters collected were: age, sex, drug, previous chemotherapy, progression-free survival (PFS) and economic spending. Data were collected from the Electronic Prescription Software Prisma(®) and the program of electronic patient records Diraya(®) and afterwards, organised in an Excel(®) base design for this study. RESULTS: A total of 74 patients with a median age of 76 years, 53 chemotherapy-naive and 21 chemotherapy-treated, were included. Fifty-nine patients were treated with abiraterone and 15 with enzalutamide. The mean PFS was 12.3 months with 49.2% of 1 year PFS. However, in the group of chemotherapy-naive patients it was 15 months, with 56% of 1 year PFS and 9.6 months (28% of 1 year PFS) in chemotherapy-treated patients. No difference was found between abiraterone group (12.4 PFS) and the enzalutamide group (12 PFS) nor in the age of the groups where PFS was 13 months in patients younger than 75 years and 12 months in those older than 75. The cost of treatment/patient was €35 559 and the total expenditure was €2,631,366 (2% of the total pharmacy service budget). CONCLUSION: The results of the effectiveness regarding PFS are lower than the ones obtained in the pivotal studies ‘301 and 302’ (abiraterone) and ‘PREVAIL and AFFIRM (enzalutamide). Chemoterapy-naïve patients have better PFS than chemotherapy-treated and there is no difference between the abiraterone group and the enzalutamide group. The cost of abiraterone and enzalutamida per life-year gained were less than €30 000. REFERENCES AND/OR ACKNOWLEDGEMENTS: Pivotal study 301 & 302 Pivotal study PREVAIl & AFFIRM No conflict of interest